1998
DOI: 10.1038/sj.bjp.0701756
|View full text |Cite
|
Sign up to set email alerts
|

Binding of KATP channel modulators in rat cardiac membranes

Abstract: 1 The binding of [ 3 H]-P1075, a potent opener of adenosine-5'-triphosphate-(ATP)-sensitive K + channels, was studied in a crude heart membrane preparation of the rat, at 378C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
0
19
1
Order By: Relevance
“…However, an early study showed that AMP-PNP alone did not affect GBC binding, but could partially rescue or reverse ATP-induced switching (58). Extending these observations showed that MgAMP-PNP alone, at concentrations far in excess of the IC 50 for MgATP, does not support conformational change, but will reverse ATP-induced switching. These results are consistent with a structural study of an asymmetric bacterial ABC protein, TM287-TM288 from T. maritima, which shows that one molecule of AMP-PNP binds to the noncanonical NBD, where it impairs subsequent NBD dimerization and thus switching to outward-facing conformations (36) and with data on cystic fibrosis transmembrane conductance regulator showing preferential binding at NBD1 (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…However, an early study showed that AMP-PNP alone did not affect GBC binding, but could partially rescue or reverse ATP-induced switching (58). Extending these observations showed that MgAMP-PNP alone, at concentrations far in excess of the IC 50 for MgATP, does not support conformational change, but will reverse ATP-induced switching. These results are consistent with a structural study of an asymmetric bacterial ABC protein, TM287-TM288 from T. maritima, which shows that one molecule of AMP-PNP binds to the noncanonical NBD, where it impairs subsequent NBD dimerization and thus switching to outward-facing conformations (36) and with data on cystic fibrosis transmembrane conductance regulator showing preferential binding at NBD1 (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with MgATP included a creatine phosphokinasebased ATP-regenerating system to maintain a constant concentration of ATP over the 30-min incubation (34). The stabil-ity of ATP levels was verified using luciferase assays (Sigma; see supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Membranes (300 g/tube) were incubated in a total assay volume of 0.25 ml in assay buffer containing an ATP regeneration system (20 mM creatine phosphate, 50 U of creatine phosphokinase, and 1 mM Na 2 ATP) at 37°C for 90 min. These conditions have been previously employed wherein the levels of ATP are consistently maintained because free ADP is converted back to ATP by creatine phosphate and creatine is regenerated to creatine phosphate by the enzyme creatine phosphokinase (Gopalakrishnan et al, 1991;Loffler-Walz and Quast, 1998). To determine the optimal ATP dependence for maximal specific binding, the assay mixture was incubated with varying concentrations of Na 2 ATP (0.01-3 mM).…”
Section: Methodsmentioning
confidence: 99%